The numerical miracle in the Holy Quran (Comprehensive Journal of Science, 2026)
This research addresses the topic of (Numerical Miracles in the Holy Qur’an). The study follows the descriptive-analytical method required by the nature of the research, through collecting information, describing it, analyzing it, and deriving meanings from it.It also adopts the comparative method to clarify the differences between the various aspects of miraculousness, as well as the critical method to present and analyze the differing opinions of both supporters and opponents in an objective scientific manner.The research examines the concept of numerical miraculousness and distinguishes it from scientific and rhetorical miraculousness. It raises the question of whether numerical harmony in the Qur’an constitutes genuine evidence of its miraculous nature, and to what extent numerical miraculousness can be considered a legitimate and scientifically acceptable aspect of Qur'an miracle.To answer these questions, the study is divided into an introduction, several main sections, and a conclusion. The sections discuss the concept of numerical miraculousness, its principles and guidelines, the approaches followed in studying it, and the views of some scholars In the conclusion, the study presents several findings, the most important of which are1. The Holy Qur’an does not explicitly describe itself using the term “miracle” in its verses and words; rather, this is conveyed through its verses and proofs.2. The purpose of miraculousness is not the miracle itself, but to establish certainty that the Qur’an is the Word of God and not a human creation.3. Miraculousness requires reflection and insight to uncover the numerical patterns and systems reflected in the coherence of its surahs, verses, and words.4. There are numerous evidences and indications of numerical miraculousness, whether from the text itself or from the statements of scholars.
Keywords: Numerical Miraculousness . Disjointed Letters Numerical Harmony Qur'an Verses